Investigation of the effect of magnetic field and ultrasound on biological systems - Bondarenko, I.S.; Bogdan, O.N. (Radiotekhnika, 2018)
The use of ultrasound (US) and magnetic field (MP) occupies an important place in biomagnetic technologies. Data on the use in medicine of one of the little-known in the literature methods of sharing US and permanent MP are presented. The results of such use are described. The analysis of new approaches for studying the properties of the biological environment and their application for solving the problem of drug directional transport is performed.